أدوات السياسة النقدية في الجزائر بعد صدور قانون النقد و القرض 90 / 10 - مدوخ, ماجدة (Sciences humaines; Vol. 23 (2011): SCIENCES HUMAINES)
انتهجت الجزائر في إطار تصحيح وضعيتها الاقتصادية مجموعة من السياسات الإصلاحية سواءا أكانت ذاتية والتي شكل قانون النقد والقرض فيها أهم إصلاح في تاريخ السياسة النقدية الجزائرية أم مدعمة من طرف الهيئات المالية الدولية، وكان نتاج هذه السياسات استخدام بنك الجزائر مجموعة من الأدوات المباشرة و غير المباشرة  لتعديل سيولة النظام المصرفي و مراقبة نمو الاقتصاد؛ فجاءت هذه الدراسة للتعرف على هذه الأدوات النقدية، وخاصة غير المباشرة منها، والمستحدثة مؤخرا.                   Pursued Algeria within the framework of correction and repositioning of the economic set of reform policies, whether be it self, which form the Code of Money and Credit in which the most important reform in the history of monetary policy Algerian or supported by international financial bodies, and was the product of these policies, the use of the Bank of Algeria set of tools of direct and indirect modification liquidity of the banking system and control the growth of the economy; came of this study to identify these monetary instruments, especially the indirect ones, and updated recently.